2012
DOI: 10.1017/jfm.2012.102
|View full text |Cite
|
Sign up to set email alerts
|

Motion of red blood cells near microvessel walls: effects of a porous wall layer

Abstract: A two-dimensional model is used to simulate the motion and deformation of a single mammalian red blood cell (RBC) flowing close to the wall of a microvessel, taking into account the effects of a porous endothelial surface layer (ESL) lining the vessel wall. Migration of RBCs away from the wall leads to the formation of a cell-depleted layer near the wall, which has a large effect on the resistance to blood flow in microvessels. The objective is to examine the mechanical factors causing this migration, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 43 publications
3
35
0
Order By: Relevance
“…Furthermore, the endothelial surface layer (ESL i.e. macromolecular layer lining the endothelial surface) was found to play an important role on blood flow resistance and its dependence to the flow rates515253. In our microvascular models we were not able to model the ESL, however some promising results have been recently shown using single brush-coated micro-channels as in vitro ESL model54.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, the endothelial surface layer (ESL i.e. macromolecular layer lining the endothelial surface) was found to play an important role on blood flow resistance and its dependence to the flow rates515253. In our microvascular models we were not able to model the ESL, however some promising results have been recently shown using single brush-coated micro-channels as in vitro ESL model54.…”
Section: Discussionmentioning
confidence: 96%
“…In such cases, the forces driving cells away from the wall may be highly sensitive to the shape of the RBC in regions where it is closest to the wall. The theory for generation of lift forces on deformable particles close to solid boundaries according to lubrication theory [53] may be helpful in obtaining insight into the relationship between the deformation of RBCs that approach the walls and the resulting generation of lift forces [20]. …”
Section: Theoretical Analysis Of Blood Flow In Narrow Tubesmentioning
confidence: 99%
“…Beaucourt et al [3] modeled the interactions of rigid and deformable vesicles with a compressible but impermeable wall substrate, representing the ESL. Conversely, Hariprasad and Secomb [20] considered the layer to be permeable but of fixed width, and showed that the rate of lateral migration of two-dimensional model RBCs decreased with increasing permeability of the layer.…”
Section: Theoretical Analysis Of Blood Flow In Narrow Tubesmentioning
confidence: 99%
“…Doddi and Bagchi [13] examined the lateral migration of a capsule in a Poiseuille flow with parallel plate geometry, but again, the effects of two walls in addition to the shear gradient could not be examined separately. Hariprasad and Secomb [14] explored the motion of a two-dimensional viscoelastic particle resembling a capsule in a microchannel with a porous layer representing the glycocalyx. Most recently, Singh et al [15] investigated * yimai@pfsl.mech.tohoku.ac.jp the lateral migration of a capsule near a wall in a parallel-plate Couette flow at small Reynolds number using a front-tracking method.…”
Section: Introductionmentioning
confidence: 99%